CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY: ANEXAMINATION IN ENERGY AND MINING COMPANIES - Elfira, Gita; Tasman, Abel (Jurnal Akuntansi Syariah (JAkSya), 2024)
This study aims to examine the effect of Corporate Governance, proxied by women on board, board activity, and sustainability committee, on Corporate Social Responsibility (CSR). The population consists of 86 energy and mining companies listed on the Indonesia Stock Exchange from 2019-2022. The sample was selected using purposive sampling, resulting in 18 companies with 72 observations. Secondary data was obtained from the Indonesia Stock Exchange website (www.idx.co.id) and the websites of the sampled companies. Data analysis was conducted using panel data regression with Eviews12 software. The results show that women on board, and board activity have a positive but insignificant effect on CSR, while the sustainability committee has a positive and significant effect on CSR.